Rhamphothrips genus-group in China, with description of two new species and two new records (Thysanoptera: Thripidae) - Li, Yajin; Liu, Zhuocheng; Zhang, Hongrui (Zootaxa, 2021)
Amalothrips bifurcus sp.n. is described from Southwestern China as the third species of Amalothrips, characterized by the forked sense cone on antennal segments III–IV. Rhamphothrips yunnanensis sp.n. is described as the second known species of Rhamphothrips in which the male has laterally on the mesosternum one thorn-like seta and one stout shaded seta. Two species, Amalothrips noorazlani Ng and Parexothrips palumai Mound, are newly recorded from China.